Evaluación de estándares de consumo en energía y macronutrientes de los principales menús consumidos, en los diferentes estratos socioeconómicos de la ciudad de Lima - Perú - Rodriguez Carranza, Jose Luis (2019)
The present research work is non-experimental, cross-sectional and descriptive in nature and was aimed at determining and evaluating the consumption standards in energy and macronutrients (proteins, fats and carbohydrates) of the main menus consumed, in the different socio-economic strata of the City of Lima - Peru. To achieve this goal, the amount of energy and macronutrients found in the menus was analyzed and multivariate analysis was used to examine the relationship of energy and macronutrients, with their different strata, as well as in obtaining classification functions, which allow classifying the menus, in the different socioeconomic strata according to the amount of energy and macronutrients contributed. Descriptive statistics were used to obtain measurements, tables and figures, which allowed us to compare the energy and macronutrients contribution of the menus, with the recommended daily consumption requirements. The study population is made up of the set of the main food dishes (menus) that are consumed at lunch, in the restaurants of the different socioeconomic strata of the city of Lima - Peru, from which a sample of 599 was taken dishes. It was generally concluded that the consumption standards in terms of energy and macronutrients of the menus are different in each socioeconomic stratum, noting that in some strata they do not cover the recommended intake standards, with an emphasis on the protein which presents values above what is recommended daily